2014
DOI: 10.1038/ja.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Anthracimycin activity against contemporary methicillin-resistant Staphylococcus aureus

Abstract: Anthracimycin is a recently discovered novel marine-derived compound with activity against Bacillus anthracis. We tested anthracimycin against an expanded panel of Staphylococcus aureus strains in vitro and in vivo. All strains of S. aureus tested, including methicillin-sensitive (MSSA), methicillin-resistant (MRSA), and vancomycin-resistant strains of S. aureus were sensitive to anthracimycin at minimum inhibitory concentrations (MIC) of < 0.25 mg/L. Although its post-antibiotic effects were minimal, anthraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Traditional checkerboard and time-kill assays were performed as previously described (10). Overnight cultures of P. aeruginosa (in LB) and S. aureus (in THB) were grown at 37°C, pelleted, washed twice, and resuspended in phosphatebuffered saline (PBS) to an OD 600 of 0.40.…”
Section: Preservatives and Reagentsmentioning
confidence: 99%
“…Traditional checkerboard and time-kill assays were performed as previously described (10). Overnight cultures of P. aeruginosa (in LB) and S. aureus (in THB) were grown at 37°C, pelleted, washed twice, and resuspended in phosphatebuffered saline (PBS) to an OD 600 of 0.40.…”
Section: Preservatives and Reagentsmentioning
confidence: 99%
“…Although somewhat similar in structure to chlorotonil (2), anthracimycin is a potent antibacterial metabolite with potential in the treatment of Grampositive pathogens such as Bacillus anthracis and methicillin-resistant Staphylococcus aureus (MRSA). That the compound shows promising preliminary activity in vivo (MRSA) [7] and that the dichloro derivative 3 has surprising activity against problematic Gram-negative pathogens, suggests that there could be significant potential utility found in this new antibacterial structure class. X-ray drawing of anthracimycin illustrating its absolute configuration.…”
mentioning
confidence: 99%
“…While the mechanism of action remains to be fully defined, it has been observed that the compound inhibits DNA/RNA synthesis in metabolic labeling experiments. [7] Follow up gel-based studies demonstrated that the nucleic acid inhibition does not likely occur through DNA intercalation. [7] Despite a large MIC shift in the presence of mouse serum, early in vivo results from MRSA infected CD1 mice showed that 1 provided significant protection (90% survival) at 10 mpK.…”
mentioning
confidence: 99%
See 2 more Smart Citations